Non-puerperal uterine inversion with submucous fibroid - A rare case report (Indian Journal of Case Reports, 2018)
Uterine inversion is an unusual, rare entity in which the uterus descends in reverse direction exposing endometrial surface through the cervix and classified as puerperal or obstetric and non-puerperal or gynecological inversion. Non-puerperal uterine inversion is very rare and often clinically misdiagnosed by the clinician. Cervix remains drawn up thus making the vaginal part of cervix difficult to palpate. Acute inversion usually occurs in the 3rd stage of the labor and is an obstetric emergency. Diagnosis is based on the clinical and imaging techniques. We report a case of a postmenopausal non-puerperal uterine inversion secondary to submucous fibroid and its successful management.